Teori Belajar Perkembangan Kognitiv Lev Vygotsky dan Implikasinya dalam Pembelajaran - Ivo Retna Wardani Wardani; Mirza Immama Putri Zuani; Nur Kholis (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The Learning Process Cannot be separated from cognitive, social and cultural development. One of the figures who discussed cognitive devolopment was Lev Vygotsky, in which Lev Vygotsky argued that children’s knowledge is influenced by their environment,that knowledge is obtained by students from interactions with the surrounding environment. So it needs to be discussed about how cognitive development, the theory of cognitive development according to Vygotsky and the implications for learning. With the aim of being able to describe the theory of cognitive development according to Lev Vygotsky and the implications for learning. The method used in this writing is a qualitative method in the form of a description with a library research approach. The results of this study state that there are three theories of cognitive development according to Vygotsky, namely through the Zona of Proximal Development (ZPD), namely the distance between the actual level of development and potential development, scaffolding namely assistance from people who are more competent and language and thoughts which are the beginning of communication. Good quality so that the implications in a teacher’s learning adapt to the cognitive development of children and design collaborative and cooperative learning. Keywords: Cognitive, Lygotsky, Learning